Application of “omics” sciences to the prediction of bone metastases from breast cancer: State of the art - Marica Gentile; Antonella Centonza; Domenica Lovero; Raffaele Palmirotta; Camillo Porta; Franco Silvestris; Stella D'Oronzo (Journal of Bone Oncology, 2021)
Breast cancer (BC) is the most frequent malignancy and the first cause of cancer-related death in women.The majority of patients with advanced BC develop skeletal metastases which may ultimately lead to serious complications, termed skeletal-related events, that often dramatically impact on quality of life and survival.Therefore, the identification of biomarkers able to stratify BC patient risk to develop bone metastases (BM) is fundamental to define personalized diagnostic and therapeutic strategies, possibly at the earliest stages of the disease.In this regard, the advent of “omics” sciences boosted the investigation of several putative biomarkers of BC osteotropism, including deregulated genes, proteins and microRNAs.The present review revisits the current knowledge on BM development in BC and the most recent studies exploring potential BM-predicting biomarkers, based on the application of omics sciences to the study of primary breast malignancies.